Species introductions through coconut fibre : Dactyloctenium aegyptium and Glinus oppositifolius, new records for the Balearic Islands, Spain - Cerrato, Marcello Dante (Array, 2021)
Based on plant material collected in the forest nursery of the Balearic Island Forestry Center (CEFOR) for autochthonous plant production and the University of the Balearic Islands experimental facilities, two new plant records are presented for the Mediterranean island of Mallorca. Dactyloctenium aegyptium, an invasive grass previously recorded in other areas of the Mediterranean basin, and Glinus oppositifolius, a new record for the European flora. In both cases the species are presumed to have arrived through contaminated batches of the coconut fibre substrate used in both facilities.